Characterisation for differential wear between left and right flank faces in turning large pitch internal thread. (2018) - Jiang, B.; Xu, T.; Li, Z.; Gu, Y.P.; He, T.T.
In turning large pitch internal thread, there are obvious differences between the wear on the same tool's left and right flank faces, which decrease the tool life and the consistency of machining surface quality of threads. Force equations of tool's left and right cutting edges are used to reveal their differences in mechanical condition. Adopting axial direction cutting method, the flank wear experiment is carried to obtain its characteristics of left and right cutting edges and the time-domain signals of tool vibration. During the formation of differential wear of left and right flank faces, the stress state and the vibration of cutting tool are analysed. Finally, distribution functions of flank wear widths are established to reveal the change characteristics of wear width along the cutting edge and the cutting stroke and quantitatively describe the wear processes and differences of left and right flank faces.